MOBILISING MUSLIM ORGANISATIONS AMID THE PANDEMIC IN INDONESIA - Ahmad Suaedy (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2022)
Collective action to protect individuals from all forms of threatening causes, including the Covid-19 pandemic, is urgently needed. The Covid-19 pandemic urged religious practices and traditions to adapt to a situation where a series of health protocols must be observed. In order to prevent the spread, World Health Organisation (WHO) issued strict health protocol rules. Some of these rules seem to be contradicted to traditions and religious practices. This article tries to investigate the ways religious societies react and respond to the health crisis caused by Covid-19. In this respect, this paper strives to answer the questions of how Indonesian Muslims respond to the pandemic of Covid-19, how religion contributes to the prevention of transmission and infection, and overcomes the social problems impacted by the pandemic, and to analyze obstacles faced by Indonesian Muslims to enhance collective awareness to the danger of the Covid-19 pandemic. This article argues that civil or non-governmental religious leaders and groups, in general, play an important role to prevent and overcome the pandemic and after because of their independency to make decisions and awareness to the severity of the Covid-19 pandemic. The involvement of religious leaders who have authority at the grassroots level strengthens the legitimacy of the obligation to comply with health protocols and has succeeded in reducing the rate of transmission and death and increasing healing. Religious authority owned by clergy at lower levels has also encouraged increased participation in social solidarity which is demanded instead to depart from diversity and not similarities, among others due to Covid-19.